2015
DOI: 10.1021/acs.analchem.5b00714
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Colorimetric Sensor Array: Single Ionic Liquid for Solvent Discrimination

Abstract: There is a continuing need to develop high-performance sensors for monitoring organic solvents, primarily due to the environmental impact of such compounds. In this regard, colorimetric sensors have been a subject of intense research for such applications. Herein, we report a unique virtual colorimetric sensor array based on a single ionic liquid (IL) for accurate detection and identification of similar organic solvents and mixtures of such solvents. In this study, we employ eight alcohols and seven binary mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…1,2 In particular, the use of ILs for electrochemical applications has been in focus for energy storage, such as super-capacitors and/or battery materials, [3][4][5] in single molecule detection, 6 and colorimetric sensing. 7 In all cases, furthering the understanding of charge accumulation and dissipation on electrode-electrolyte interfaces is of utmost importance. It is well-known that when an electrified solid interface is brought into contact with ionic conductors, the surface accumulates opposite charges and forms an electrical double layer (EDL) at the interface, and numerous advanced electrochemical, spectroscopic, microscopic and theoretical/ simulation techniques have been employed towards advancing the basic understanding of the interface properties of ILs, especially when they are electrified.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In particular, the use of ILs for electrochemical applications has been in focus for energy storage, such as super-capacitors and/or battery materials, [3][4][5] in single molecule detection, 6 and colorimetric sensing. 7 In all cases, furthering the understanding of charge accumulation and dissipation on electrode-electrolyte interfaces is of utmost importance. It is well-known that when an electrified solid interface is brought into contact with ionic conductors, the surface accumulates opposite charges and forms an electrical double layer (EDL) at the interface, and numerous advanced electrochemical, spectroscopic, microscopic and theoretical/ simulation techniques have been employed towards advancing the basic understanding of the interface properties of ILs, especially when they are electrified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previously mentioned RP‐type phase, monolithic supports can take use of a variety of other interactions like: IEC , HILIC , HIC , fluorinated tags separation , IMAC , affinity chromatography , imprinted phases , chiral separation . Although functional groups on a support determine the type of separation, an interplay within different principles can lead to a novel approach.…”
Section: General Aspects Of Monolithic Materialsmentioning
confidence: 99%
“…[21][22][23][24][25] Several interesting ILbased sensor applications have been reported in the literature. [25][26][27][28][29][30][31][32] For example, Ts eng et al developed sensing ionic liquids (SILs) for chemoselective detection of gases by using aq uartz crystal microbalance (QCM). [26] Seyamae tal.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Using similar chemistry,W arner and co-workers expanded this approach to develop ac olorimetric sensora rray based on as ingle IL for the accurated etectiona nd identification of chemically similaro rganic solvents andm ixtures of such solvents. [30] Thin 1-alkyl-3-methylimidazolium bis(trifluoromethane sulfonyl)imide ([Tf 2 N] À )o rt etrafluoroborate ([BF 4 ] À )I L films were used in concert with aQ CM for vapor sensing. [31] Recently,K wak et al found that an IL formedb yi on-pairing of anionic Au 25 clusters stabilizedw ith (3-mercaptopropyl)sulfonate (MPS-Au 25 )w ith 1-decyl-3-methylimidazolium (DMIm) cations, acted as av ersatile matrix for amperometric enzyme biosensors to detect glucose.…”
Section: Introductionmentioning
confidence: 99%